Mutually Dependent Clustering of SynDIG4/PRRT1 and AMPA Receptor Subunits GluA1 and GluA2 in Heterologous Cells and Primary Neurons - Plambeck, Kristopher E.; He, Chun-Wei; Navarro, Hector H.; Díaz, Elva (Frontiers in Molecular Neuroscience, 2022)
Regulation of AMPA-type glutamate receptors (AMPARs) at synapses is a predominant mechanism for regulating synaptic strength. We identified the transmembrane protein Synapse Differentiation Induced Gene 1 (SynDIG1; SD1) as an AMPAR interacting protein that regulates excitatory synaptic strength and AMPAR number both in vitro and in vivo. The related protein SynDIG4 (SD4; also known as PRRT1) was identified in several independent proteomic screens in complex with AMPARs, suggesting it may function as an AMPAR auxiliary factor. Here, we show that co-expression of SD4 with GluA1 or GluA2 homomeric AMPARs in COS cells leads to a 50% or 33% increase in the mean area of AMPAR puncta, respectively. This effect is accentuated when AMPAR puncta are stratified for co-localization with SD4, resulting in a 100% and 65% increase in GluA1 and GluA2 puncta, respectively. Chimeric proteins expressing only the membrane bound domain of SD4 co-expressed with full-length GluA1 or GluA2 recapitulated the effects of wild-type SD4. Additionally, the mean puncta area of GluA1 or GluA2 chimeras expressing the membrane and C-terminal domains increased significantly when co-localized with wild-type SD4. Similarly, co-expression of GluA1 or GluA2 with SD4 results in a significant increase in the mean area of SD4 puncta co-localized with GluA1 or GluA2, respectively. Lastly, we observed a significant increase in co-localization of SD4 with GluA1 after glycine induced LTP. The mean size of GluA1 puncta was significantly increased when stratified, indicating that co-localization with SD4 increases synaptic GluA1 cluster size during LTP. These data indicate mutually-dependent clustering of SD4 and AMPAR subunits both in COS cells and primary hippocampal neurons, suggesting a mechanism for increased synaptic strength during chemical LTP.